2004
DOI: 10.1002/ajh.20187
|View full text |Cite
|
Sign up to set email alerts
|

Serum ionized magnesium levels and ionized calcium‐to‐magnesium ratios in adult patients with sickle cell anemia

Abstract: Low levels of total magnesium in sickle cell erythrocytes have been linked to increased sickling due to cell dehydration. We tested the null hypothesis that adult sickle cell anemia (SCA) patients have the same serum level of ionized Mg (Mg 2+ ) and Ca 2+ /Mg 2+ ratio as healthy African Americans (AA) and healthy Caucasians (CAUC). We measured serum Mg 2+ and ionized calcium (Ca 2+ ) with ion-selective electrodes and calculated the serum Ca 2+ /Mg 2+ ratios in patients with SCA and control groups (AA and CAUC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
2
17
0
1
Order By: Relevance
“…Some studies have measured normal circulating levels74,83 while others are reported to be low 84. Low levels of total Mg in sickle cell erythrocytes have been associated with increased sickling due to propensity for red cell dehydration and hence, increased HbS polymerization 7,85.…”
Section: Direct Evidence For Nutritional Deficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have measured normal circulating levels74,83 while others are reported to be low 84. Low levels of total Mg in sickle cell erythrocytes have been associated with increased sickling due to propensity for red cell dehydration and hence, increased HbS polymerization 7,85.…”
Section: Direct Evidence For Nutritional Deficienciesmentioning
confidence: 99%
“…They reported that the participants with HbSS had significantly lower levels of serum Mg 2+ (0.52 ± 0.05) compared with healthy ethnicity matched controls (0.57 ± 0.04) and Caucasian controls (0.62 ± 0.03), P < 0.001. By measuring serum Mg 2+ and Ca 2+ , they were able to define a subset of HbSS patients with hypomagnesemia and elevated Ca 2+ /Mg 2+ ratios, who might benefit from magnesium supplementation 84. In another study, Brousseu et al reported a decrease in the length of hospital stay from approximately 5 days to an average of 3 days ( P < 0.01) in children admitted to the hospital for painful crisis, who were given IV Mg 86.…”
Section: Direct Evidence For Nutritional Deficienciesmentioning
confidence: 99%
“…Zinc supplementation not only improved growth and weight of SCD children, but also gave a boost to their immunity by offering antibacterial protection, thereby making its supplementation essential. Besides zinc, magnesium was found to protect against losses of water and potassium in SCD patients [ 39 , 40 ]. Magnesium deficiency was found to increase episodes of sickling by causing cell dehydration in sickled erythrocytes [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides zinc, magnesium was found to protect against losses of water and potassium in SCD patients [ 39 , 40 ]. Magnesium deficiency was found to increase episodes of sickling by causing cell dehydration in sickled erythrocytes [ 40 ]. In SCD patients It has been found that magnesium supplementation reduced the number of dense erythrocytes and also improved the erythrocyte membrane transport abnormalities of patients with SCD [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc deficiency is a common nutritional problem in sickle cell disease, so supplements may be important. Magnesium protects against potassium and water loss in sickle cells [19, 72, 73]. In view of these findings, it can be concluded that Ciklavit may cause a reduction in bone pains (painful crises) and may ameliorate the adverse effect of sickle cell anemia on the liver.…”
Section: Herbal Preparations Already In Use As Government-approvedmentioning
confidence: 99%